Manejo postcosecha del cultivo de zanahoria (Daucus carota L.) para su comercialización - Celi Heredia, Arnold Jacob (2021)
This document detailed the postharvest handling of carrot (Daucus carota L.) for commercialization. The carrot is one of the most cultivated vegetables in the world. Its consumption has spread widely, since it is currently available in the markets throughout the year. The consumed part of the carrot is its root, of which there are multiple forms and flavors. It stands out for its content of carotene and vitamins A, B and C. The carrot is sold directly by farmers, trying to improve their economic income through the direct distribution and sale of the raw material. The conclusions determine that postharvest is the set of operations and functions between production and consumption developed by different actors with the aim of achieving an effective and efficient supply of carrots. This includes preparation for market (cleaning, sorting and packing), transport and marketing. It is a system that is closely related to productive activities and attentive to the needs and demand of consumers. All the previous productive and environmental aspects condition the quality of the product and eventually that which reaches the consumer, since in the post-harvest the quality cannot be improved but only standardized as well as reducing the rate of natural deterioration after harvest and because carrots are eaten fresh, the hygiene of the facilities and equipment as well as operations are important to avoid contamination by microorganisms not visible to the naked eye or detectable through changes in appearance, taste, color or other external characteristics , but harmful to health.